2013
DOI: 10.1039/c2cc36626f
|View full text |Cite
|
Sign up to set email alerts
|

A thiazolothiazole based Cu2+selective colorimetric and fluorescent sensor via unique radical formation

Abstract: A novel thiazolothiazole-based Cu(2+) colorimetric and fluorescent sensor is reported. A highly selective colorimetric change from yellow to dark green was observed among various metal ions after adding Cu(2+). Unique radical formation can engender these highly selective colorimetric and fluorescent changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(42 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…Instead, focus has largely been placed on the incorporation of TzTz into charge transfer systems by coupling the electron accepting ( n ‐type) behavior of the moiety with that of an electron donor ( p ‐type), creating extended organic compounds displaying sought‐after electrical properties 11. Though initially focused on biological activity, the discovery of the photophysical properties of TzTz in organic systems has led to the creation of semiconducting polymers,12 field‐effect transistors8a and optical devices 8b…”
Section: Introductionmentioning
confidence: 99%
“…Instead, focus has largely been placed on the incorporation of TzTz into charge transfer systems by coupling the electron accepting ( n ‐type) behavior of the moiety with that of an electron donor ( p ‐type), creating extended organic compounds displaying sought‐after electrical properties 11. Though initially focused on biological activity, the discovery of the photophysical properties of TzTz in organic systems has led to the creation of semiconducting polymers,12 field‐effect transistors8a and optical devices 8b…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that borohydride (NaBH 4 ) was able to turn the more oxidative Hg 2+ into Hg 0 , these less oxidative ions (Cu 2+ , Co 2+ , Ni 2+ , et al ) remained unaffected during the process [29], so in order to detected Cu 2+ , we used NaBH 4 as masking regent to eliminate the related quenching from Hg 2+ ion.…”
Section: Study the Interaction Of Dpbt And Cu 2+mentioning
confidence: 99%
“…In recent years, many fluorescence probes for selective and sensitive detection of Hg 2+ or Cu 2+ have been reported [23][24][25][26][27][28][29], most of them can be utilized to directly detect low concentration of Hg 2+ or Cu 2+ in real environmental samples and in living cells. To the best of our knowledge, some fluorescence sensors for simultaneous Hg 2+ and Cu 2+ ions have been reported [30][31][32], but there are many aspects left to be improved, such as narrow pH range, low water solubility, complex preparation and lack of sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, a number of sensors used for the assay of Cu 2+ have been developed, such as electrochemical and electrochemical luminescence sensors [16,17], colorimetric assays [18,19], atomic absorption assays [20], and fluorescent detections [21][22][23][24][25][26][27]. Among these reported methods, the fluorescence technique has been studied in recent years, owing to several superior advantages i.e., high sensitivity and low detection limit, excellent stability and selectivity and low-cost.…”
Section: Introductionmentioning
confidence: 98%